Changes in Tactile Function During Intensive Bimanual Training in Children With Unilateral Spastic Cerebral Palsy. (March 2018) - Saussez, Geoffroy; Van Laethem, Marie; Bleyenheuft, Yannick
Recently, an intensive bimanual intervention using sensory enriched materials resulted in improved tactile function in children with unilateral spastic cerebral palsy (USCP), raising the question of whether the observed tactile function improvement was due to the sensory enriched environment or the bimanual intervention per se. The present study investigates whether a bimanual intensive intervention improves tactile function. Nineteen children with USCP received 90 hours of bimanual training without enriched environment. Primary outcomes: Manual Form Perception Test/MFPT, Grating Orientation Task/GOT. Children were assessed before, after the training, and at the 4-month follow-up. Significant improvements were observed in MFPT for the more affected hand ( P = .015). Larger stereognosis/MFPT improvements correlated with poorer baseline motor function. Intensive bimanual training alone was sufficient to improve stereognosis, though no improvement in GOT was observed. Present and previously published findings suggest that environmental tactile enrichment incorporated into a bimanual motor training may be needed to improve spatial discrimination/GOT in children with USCP.